Corticotropin Releasing Factor in the Bed Nucleus of the Stria Terminalis in Socially Defeated and Non-stressed Mice with a History of Chronic Alcohol Intake - Albrechet-Souza, Lucas; Viola, Thiago W.; Grassi-Oliveira, Rodrigo; Miczek, Klaus A.; de Almeida, Rosa M. M. (Frontiers in Pharmacology, 2017)
Stress exposure has been identified as one risk factor for alcohol abuse that may facilitate the transition from social or regulated use to the development of alcohol dependence. Preclinical studies have shown that dysregulation of the corticotropin releasing factor (CRF) neurotransmission has been implicated in stress-related psychopathologies such as depression and anxiety, and may affect alcohol consumption. The bed nucleus of the stria terminalis (BNST) contains CRF-producing neurons which seem to be sensitive to stress. In this study, adult male C57BL/6 mice previously defeated in resident-intruder confrontations were evaluated in the elevated plus-maze and tail suspension test. Mice were also tested for sweet solution intake before and after social stress. After having had continuous access to ethanol (20% weight/volume) for four weeks, control and stressed mice had CRF type 1 (CRFR1) or type 2 (CRFR2) receptor antagonists infused into the BNST and then had access to ethanol for 24 hours. In separate cohorts of control and stressed mice, we assessed mRNA levels of BNST CRF, CRFR1 and CRFR2. Stressed mice increased their intake of sweet solution after ten sessions of social defeat and showed reduced activity in the open arms of the elevated plus-maze. When tested for ethanol consumption, stressed mice persistently drank significantly more than controls during the four weeks of access. Also, social stress induced higher BNST CRF mRNA levels. The selective blockade of BNST CRFR1 with CP376,395 effectively reduced alcohol drinking in non-stressed mice, whereas the selective CRFR2 antagonist astressin2B produced a dose-dependent increase in ethanol consumption in both non-stressed controls and stressed mice. The ten-day episodic defeat stress used here elicited anxiety- but not depressive-like behaviors, and promoted an increase in ethanol drinking. CRF-CRFR1 signaling in the BNST seems to underlie ethanol intake in non-stressed mice, whereas CRFR2 modulates alcohol consumption in both socially defeated and non-stressed mice with a history of chronic intake.